Kepedulian dan Pemahaman dalam Penerapan Green Accounting pada UKM Tahu di Kecamatan Batuan Kabupaten Sumenep - Mahbubah, Istiyanatul; Malia, Evi; Azaro, Khoirin; Yusna, Yusna; Syahputra, Ferdian Eko; Fibriani, Rudiana (Unversitas Islam Madura, 2025)
The purpose of this study was to determine the awareness and understanding in the implementation of Green Accounting in tofu SMEs in Batuan District, Sumenep Regency. The type of data used in this study is primary data, namely by interviewing tofu business actors in Batuan District, Sumenep Regency. Based on the results of the interview, the understanding of tofu SME actors in Batuan District is still low because the preferences of tofu SME actors are still focused on business profits, not on product quality and environmental quality. Lack of awareness of environmental impacts that can affect the sustainability of their business is a factor causing the low level of understanding. In terms of knowledge about environmental costs, business actors have also not been able to identify what are the components of environmental costs which are also a factor causing the low understanding of SMEs.